Mesozooplankton biomass and abundance in Cyprus coastal waters and comparison with the Aegean Sea (eastern Mediterranean) - HANNIDES, C. C.S.; SIOKOU, I.; ZERVOUDAKID, S.; FRANGOULIS, C.; LANGE, M. A. (Mediterranean Marine Science, 2015)
Here we conduct the first comprehensive assessment of mesozooplankton abundance, biomass, and taxa composition in Cyprus coastal waters (Levantine Sea). Mesozooplankton abundance and biomass sampled at several locations around the island ranged from 153 – 498 individuals m-3 and 0.7 – 5.2 mg dry weight m-3, respectively, with significantly larger biomass observed in winter-early spring (March) than in summer (September). The community was dominated by calanoid and cyclopoid copepods throughout the year (80% of total numbers), with higher abundances of predatory taxa (chaetognaths and medusae) in winter and cladocerans in summer. Overall, we find that coastal mesozooplankton communities around Cyprus appear to be more similar to communities in offshore waters or those around the island of Rhodes than to communities along the mainland Levantine coast. We further highlight regional differences in the eastern Mediterranean by comparing our data with mesozooplankton in the western Aegean (Saronikos Gulf) and northeastern Aegean Sea (NEA). Distinct spatial differences were observed, for example anthropogenic influences in the Saronikos Gulf and the outflow of Modified Black Sea Water in the NEA drove generally greater biomass and abundance in these regions. Overall, our comparison supports the concept of a latitudinal gradient in oligotrophy in the eastern Mediterranean, with ultra-oligotrophic conditions found in the Levantine Sea.